Pengaruh HCE, SCE, CEE, Liquidity, dan Firm Size terhadap Firm Performance - Vania, Vica; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to empirically prove the effect of the variable human capital efficiency (HCE), structural capital efficiency (SCE), capital employed efficiency (CEE), liquidity, dan firm size to the variable firm performance, using 84 manufacturing companies listed at the Indonesia Stock Exchange in 2017-2019. Data processing in this research using software program the Eviews version 12.0. The results of the research that have been carried out on the simultaneous test shows that bahwa human capital efficiency, structural capital efficiency, capital employed efficiency, liquidity, dan firm size have a significant simultaneous effect on firm performance, while the partial significance test shows that SCE and liquidity have a significant effect on CAR, but for HCE, CEE, and firm size have no significant effect on firm performance.